Jejunoileal Atresia: A National Cohort Study - Schmedding, Andrea; Hutter, Martin; Gfroerer, Stefan; Rolle, Udo (Frontiers in Pediatrics, 2021)
Purpose: Jejunoileal atresia (JIA) is a rare disease. We aimed to determine the overall incidence of this malformation and associated malformations in a national cohort. Furthermore, we compared the treatment results of this cohort with the current literature. Methods: Data from the major health insurance company, which covers approximately 30% of the German population, were analyzed. All patients with ICD-10-Code Q41.1-9 (atresia of jejunum, ileum, other parts and not designated parts of the small bowel) who underwent any surgical procedure for small bowel were analyzed in a 10-year period between 2007 and 2016. Results: A total of 435 patients were included in the study. The incidence was 2.1 per 10,000 live births. The male:female ratio was 1:2. Sixty-four percent were premature, 21% had associated cardiac anomalies, 16% had abdominal wall defects, 7% had urogenital malformations, and 7% had cystic fibrosis. Sixty percent of all patients with jejunoileal atresia, 57% of patients with accompanying abdominal wall defects and 72% of patients with associated cystic fibrosis required ostomy as the initial procedure. In 25% of all patients, only one intestinal operation was coded. In 39% of patients, two operations were coded. Twelve percent of all patients required feeding gastrostomy or jejunostomy. Sixteen percent of all patients presented with liver-related complications, i.e., cholestasis or liver insufficiency. Six patients underwent an intestinal lengthening procedure (2 Bianchi, 4 STEP). In five patients, initial lengthening was performed within one year after the first intestinal operation. Mortality until one year after initial surgery was 5%. Of those who died, 88% were premature, 34% had cardiac anomalies and 16% had abdominal wall defects. None had cystic fibrosis. Conclusion: Patients with JIA present with low mortality but a relatively high rate of ostomies and liver complications. Our data are comparable to the literature except for the higher rate of ostomies.